Burial assemblages with small ditches (necropolis of Kobyakovo hillfort) - Larenok V.A. (Archaeoastronomy and Ancient Technologies, 2016)
Review of burial assemblages with small ditches, found during excavations of the necropolis of the Kobyakovo hillfort is presented in this article. Ground burial of the Kobyakovo hillfort located on the right high bank of the river Don. Burials with small ditches are traced on the border of the necropolis of the hillfort from the north to the south-west. They are separate from the rest of the cemetery. They do not exist in the south-east and in the central parts. They are located in those areas of the necropolis, where burial places appeared in the second century AD. The burials dated to the same time. It seems that the outskirt of the necropolis was specifically highlighted for burial with such a rite. Burial assemblages, surrounded by small ditches, have different designs, but their types coincide with the designs of other burials in the necropolis of the hillfort as a whole. In 5 cases - undercuts, 3 - catacombs and 1 - pit with shoulders. In most cases the burials were robbed, what prevented completely restore the rite. In three cases - military burials with the bones of sacrificial animals in the wells, weapons and horse gear. The deceased in the burial 7 from the excavations in 2008 was buried in a narrow wooden deck, which is rather rare in the rite of necropolis. As a result the study concluded that the necropolis of Kobyakovo hillfort is complex in its structure and content of the archaeological site, where the tradition of spiritual and material culture of the settled and nomadic population of the Lower Don of the first century AD combined, and burial assemblages with small ditches are a striking example of the influence the steppe culture on the population of Maeotian settlements.